Smoking beliefs across genders, a comparative analysis of seven European countries - Adeline Grard; Michael Schreuders; Joana Alves; Jaana M. Kinnunen; Matthias Richter; Bruno Federico; Anton Kunst; Luke Clancy; Vincent Lorant (BMC, 2019)
Abstract Background Most European countries have seen a decrease in the prevalence of adolescent smoking. This decrease has, however, been patterned by gender. Girls' smoking rates have now overtaken boys' in many European countries. The two genders may not, however, share the same smoking beliefs and this could explain differences between the genders in smoking prevalence. We describe gender differences in smoking beliefs and investigate variations between countries, along with their gender context. Methods In 2016, we conducted the SILNE R study (Smoking Inequalities Learning from Natural Experiments - Renew) in 55 schools located in seven European countries: Belgium, Italy, The Netherlands, Portugal, Finland, Ireland, and Germany. We surveyed 12,979 students aged 14-16 years (50% were girls). We classified smoking beliefs into four categories: positive individual, positive social, negative individual, and negative social beliefs. We expected girls to score higher on the last three of those categories and we hypothesized that countries with a more gender-equal culture would have less gender difference in beliefs about smoking. Results One out of two smoking beliefs differed significantly between genders. Negative social beliefs were more common in girls, while beliefs about the dating-related aspects of smoking were more common in boys. We identified Germany and Belgium as the only countries with no gender differences in any of the belief scales. No correlation was found, however, between these scales and the Gender Inequality Index. Conclusions In some countries, gender-specific interventions might be implemented; however, two opposing strategies might be used, depending on whether such programs are aimed at boys or girls.